Ovarian morphology and plasma hormonal concentration during different phases of reproductive cycle in buffaloes (Bubalus bubalis) - Bansal, Neelam; Jindal, Rajesh; Nayyar, Shashi; Malik, V S (The Indian Journal of Animal Sciences, 2011)
Gross morphological and hormonal studies were made on 30 apparently healthy adult Murra buffaloes. On the basis ,of colour, consistency and diameter of the follicles and coropa lutea observed on the surface of ovaries, animals weregrouped into follicular, early-luteal or late-luteal phases of reporductive cycle along with various ranges of corpus luteum.This categorization, was confirmed with circulating levels of gonadal hormones plasma estradiol- 17-Beta and progesterone which were  maximum (25.73 +- 9.75 pg/ml and 2.32 +-0.62 ng/ml) during presumed follicular and luteal phases, respectively.